Pengaruh Beban Kerja Terha Dan Keseimbangan Kehidupan Kerja Di Instansi X Banjarmasin - Erinna Sabila Shoulina; Rizqi Amalia Aprianty; Julaibib (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Work-life balance was one of the important aspects in supporting employee productivity and well-being. Excessive workload was often the main factor disrupting this balance, negatively affecting mental health, social relationships, and individual work performance. This study aimed to analyze whether workload affected work-life balance at Institution X in Banjarmasin. The research design used a correlational quantitative approach. The population in this study consisted of 31 people, and data collection was conducted online using Google Forms. The data were then analyzed using simple linear regression analysis. The results indicated a significant negative influence of workload on work-life balance. This means that the higher the workload employees received, the lower their ability to maintain a balance between work and personal life. Based on these findings, it was recommended that the organization improve employees' work-life balance by managing workloads more evenly and providing flexible working hours, enabling employees to better maintain harmony between professional responsibilities and personal interests.